PENGUKURAN SIFAT OPTIS AKTIF BAHAN NAFTALENA DAN ANTRASENA DALAM MEDAN LISTRIK LUAR - Fajri Inayat; Ketut Sofjan Firdausi (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Naphthalene (C10H8) and anthracene (C14H10) are simetric organic matter. Both of them predicted didn’t have electrooptic characteristic. That characteristic will appear if we induce them with external electric field. In the examination, it was used source light incandescent lamp 100 W. The external electric field generated by HV DC generator of 0-7 kV. The electrooptics characteristic was determined by measuring the change of polarization angle of light as it passed through the difference concentration of naphthalene and anthracene while they were applied by external electric field.Based on the result of observation, change of polarization angle of the light was increasing at each different potential between naphthalene (range 0,30 – 10) and anthracene (range 0,10 - 0,70). Beside that, changes of polarization angle of the light was increase linearly to the increase of naphthalene concentration, while anthracene was not. These results consider for more research to do with alternative organic materials in photonic devices.